Study of Common Allergens in Patients with Allergic Contact Dermatitis: A Hospital Based Study - Rana, Arnija; Shrestha, S; Jha, AK; Thapa, DP; Joshi, S; Amatya, B (Nepal Medical College Journal, 2021)
Allergic contact dermatitis (ACD) is one of the most common diseases presenting to the Dermatology department. The one and only method of preventing as well as treating this disease is avoidance of the allergen causing it. The identification of the allergen causing the ACD is possible by performing patch testing. The purpose of this study was to identify common allergens among patients with ACD using Indian standard series (ISS) of patch test. Clinically suspected cases of ACD were included in the hospital based cross-sectional study from January to December 2017. These cases underwent patch testing with the ISS. The study assessed the following variables: sex, age, occupation, site and positive patch test results. There were a total of 58 patients among which, 36.2% were males and 63.8% were females with a mean age of 32.36±12.51 years. Positive patch test reactions were seen in 63.0% of patients. The most common allergens were nickel sulphate (51.4%), fragrance mix (37.8%), potassium dichromate (8.1%), colophony (8.1%) and black rubber mix (8.1%). Among male, most common allergens were fragrance mix (57.1%), nickel sulphate (28.6%) and potassium dichromate (21.4%) while in female, most common allergens were nickel sulphate (65.2%) and fragrance mix (26.1%). In our study, majority of the allergens were positive. Hence, the ISS used in the study might be suitable in the context of Nepalese population. However, further similar studies on large number of patients with multiple allergens are required to determine the exact number of contact allergens prevalent in our population.